Preliminary data on the aquatic insect in Hai Van area, Thua Thien - Hue province - Trung, Hoang Dinh; Son, Le Trong; Quy, Mai Phu (Academia Journal of Biology, 2012)
This paper reported the preliminary data on biodiversity of the aquatic insects and provided a list of insect species, which are known for the first time in Hai Van area, Thua Thien - Hue province. Of the total 53 species of aquatic insects recorded belonging to 4 orders, 40 genera and 17 families the Ephemeroptera consist of 25 species making 47.17%, the Plecoptera with 11 species (20.75%), the Odonata with 10 species (18.87%) and the Trichoptera with 7 species (13.20%). The family Heptageniidae (Ephemeroptera) is the most dominant one with 8 genera (20%) and 9 species (16.98%). Of the total 17 families, the Ephemeroptera has five families (making up 29.41%), 16 genera (40% of total genera); the Plecoptera has four families (23.53% of total families), 7 genera (up to 17.50%); the Trichoptera has four families (up to 23.53% of total families), 7 genera (17.50%); the Odonata has four families (accounting for 23.53%), 10 genera (25% of total of genera). Using the similarity index Sorencen (S) to compare the homology of species composition of aquatic insects in Hai Van area with fresh water areas in Vietnam showed that the species composition of aquatic insects in the Hai Van is close to that in contigous area of Bach Ma National Park (S = 0.23). Among 145 species of insects recorded in Tam Dao NP, there are nine common species, which are recorded in Hai Van (S = 0.09). The lowest similarity coefficient (S = 0.04) in comparing the homology of species composition of aquatic insects between Sa Pa, Lao Cai and Hai Van, Thua Thien - Hue province. Probably the closeness of component of spieces in fresh water areas showed the more similar are characters of two habitats, the closer are the fauna.